Motility phenotype in a zebrafish vmat2 mutant. - Hildur Sóley Sveinsdóttir; Amanda Decker; Christian Christensen; Pablo Botella Lucena; Haraldur Þorsteinsson; Elena Richert; Valerie Helene Maier; Robert Cornell; Karl Ægir Karlsson (PLoS ONE)
In the present study, we characterize a novel zebrafish mutant of solute carrier 18A2 (slc18a2), also known as vesicular monoamine transporter 2 (vmat2), that exhibits a behavioural phenotype partially consistent with human Parkinson´s disease. At six days-post-fertilization, behaviour was analysed and demonstrated that vmat2 homozygous mutant larvae, relative to wild types, show changes in motility in a photomotor assay, altered sleep parameters, and reduced dopamine cell number. Following an abrupt lights-off stimulus mutant larvae initiate larger movements but subsequently inhibit them to a lesser extent in comparison to wild-type larvae. Conversely, during a lights-on period, the mutant larvae are hypomotile. Thigmotaxis, a preference to avoid the centre of a behavioural arena, was increased in homozygotes over heterozygotes and wild types, as was daytime sleep ratio. Furthermore, incubating mutant larvae in pramipexole or L-Dopa partially rescued the motor phenotypes, as did injecting glial cell-derived neurotrophic factor (GDNF) into their brains. This novel vmat2 model represents a tool for high throughput pharmaceutical screens for novel therapeutics, in particular those that increase monoamine transport, and for studies of the function of monoamine transporters.